Audiovisual atraumatic care and cooperative behavior among hospitalized children: A case study - Hemma Siti Rahayu; Suci Nurjanah; Putri Mahardika; Sari Artauli Lumban Toruan; Gilar Wisnu Hardi; Berlian Kusuma Dewi; Winani Winani; Bachtiar Efendi; Syariefah Waliulu; Muthahharah Muthahharah; ⁠Ine adelia (Indonesian Nursing Journal, 2026)
Background: Hospitalization is a stressful experience for children, often causing fear, anxiety, crying, and uncooperative behavior during nursing procedures. Children may perceive hospitals as threatening, particularly during invasive procedures. Audiovisual distraction is a recognized non-pharmacological atraumatic care approach to reduce distress in hospitalized children. Purpose: This study aimed to describe audiovisual atraumatic care implementation and its effect on cooperative behavior in hospitalized children. Method: This descriptive case study was conducted in the pediatric ward of RSUP Fatmawati Hospital, Jakarta, Indonesia, from March 7–12, 2022. Two children aged 3 and 10 years experiencing hospitalization-related stress were selected through purposive sampling. Data were collected via direct observation and interviews. Cooperative behavior was evaluated using an observation sheet adapted from Harsono (2006), assessing crying, refusal, facial expression, eye contact, willingness to follow instructions, and verbal responses. The intervention consisted of watching cartoons for 15 minutes and playing online games for 10 minutes, delivered twice daily for three consecutive days. Data were analyzed descriptively. Results: Before the intervention, cooperative behavior scores were 2 and 1 for Case 1 and Case 2. After three days, both cases achieved scores of 4. Observations revealed reduced crying, improved eye contact, calmer expressions, and better acceptance of nursing procedures. Given the descriptive, two-case nature of this study, findings should be interpreted cautiously, and larger studies are needed. Conclusion: Both cases showed improved cooperative behavior following audiovisual atraumatic care. Larger studies are necessary to validate these findings and establish this intervention's benefits in pediatric nursing.